THE USE OF SMALL GROUP DISCUSSION STRATEGY IN TEACHING WRITING - Salmon J Hukom (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2020)
The problems always occur in teaching and learning English as a foreign language, and these depend on teachers and students as the center of that process. The teachers have to use appropriate strategy in order to engage the students to achieve their aims of learning.In teaching writing, the teachers always use conventional way such as give the topic and ask the students to write and collect it. There is not any feedback from teachers to students’ work. Small group discussion plays important role since it helps the students to help one another to produce good quality of writing product. It also helps the students to have confidence, and the students will get sense of social values in their life.